2017
DOI: 10.1021/acsami.7b03127
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating Bone via Multifunctional Coatings: The Blending of Cell Integration and Bacterial Inhibition Properties on the Surface of Biomaterials

Abstract: In dentistry and orthopedics, it is well accepted that implant fixation is a major goal. However, an emerging concern is bacterial infection. Infection of metallic implants can be catastrophic and significantly reduce patient quality of life. Accordingly, in this work, we focus on multifunctional coatings to simultaneously address and mitigate both these problems. We have developed a tailor-made peptide-based chemical platform that integrates the well-known RGD cell adhesive sequence and the lactoferrin-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 58 publications
6
103
1
1
Order By: Relevance
“…In the first place, it is becoming evident that the biological evaluation of the osteoconductive and antibacterial potential of any new multifunctional surface will require the use of eukaryotic cell–bacteria cocultures, as the results obtained with the individual cell types may greatly differ from the more realistic, competitive scenario. In a recent study, we showed that bacteria directly inhibited the capacity of osteoblastic cells to spread and proliferate . This study indicates that bacteria and cells not only race for the surface, but “fight for it,” and makes us postulate that the interactions between these two cell types and the biomaterial surface are better referred to as “the fight for the surface.” However, the mechanisms governing these interactions are not well understood, as the majority of current methods focus on the “finish line,” but do not monitor the dynamic process of competition for the surface.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the first place, it is becoming evident that the biological evaluation of the osteoconductive and antibacterial potential of any new multifunctional surface will require the use of eukaryotic cell–bacteria cocultures, as the results obtained with the individual cell types may greatly differ from the more realistic, competitive scenario. In a recent study, we showed that bacteria directly inhibited the capacity of osteoblastic cells to spread and proliferate . This study indicates that bacteria and cells not only race for the surface, but “fight for it,” and makes us postulate that the interactions between these two cell types and the biomaterial surface are better referred to as “the fight for the surface.” However, the mechanisms governing these interactions are not well understood, as the majority of current methods focus on the “finish line,” but do not monitor the dynamic process of competition for the surface.…”
Section: Discussionmentioning
confidence: 89%
“…Using this platform we recently combined the RGD sequence with LF1‐11, an AMP derived from lactoferrin that showed excellent antibacterial properties on Ti surfaces . Such approach very effectively improved OB adhesion, proliferation, and mineralization, and inhibited S. aureus and S. sanguinis attachment and biofilm progression ( Figure ) . Importantly, the bifunctional molecule was also effective in a coculture scenario in which the surfaces were exposed to bacterial suspensions (preinfective condition) for 2 h before seeding OB‐like cells.…”
Section: Multifunctional Chemical Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been carried out focusing on bone implant modification with bioactive molecules with antimicrobial and anti‐inflammation ability such as antibiotics, metal ions, peptides, vaccines, hydrogels, and heparin via coating or immobilization chemistry. [62b,131,152,154,157–159] First, the most promising antimicrobial molecules are antibiotics. To enhance the efficacy of antibiotics, local delivery using immobilization methods has been widely investigated.…”
Section: Biomaterials For Modulation Of Infection and Inflammationmentioning
confidence: 99%
“…Silver nanoparticles have been widely used for antimicrobial activity in various fields, in which silver ions break through the bacterial cell wall and disrupt the respiration in mitochondria, attaching to the DNA to stop cell replication. [62b,152] In addition, various types of antimicrobial peptides (AMPs) derived from many proteins have been utilized, and novel applications in both physical immobilization of AMPs on the surface and chemical conjugation of AMPs have been widely investigated …”
Section: Biomaterials For Modulation Of Infection and Inflammationmentioning
confidence: 99%